Mental health problems of school children aged 14+16 years in Galle district, eight months after Tsunami - Agampodi, T.C (My University, 2006)
A descriptive cross sectional study was carried out using cluster sampling with probability proportionate to size. The study instrument consisted of a self administered questionnaire and the validated Sinhala version of strengths and difficulty questionnaire was used for the assessment of mental health problems. The prevalence of mental health problems were higher than the global prevalence and expected WHO values for the post tsunami situation. Poor relationship between parents. low levels of parental education, absence of a close person specially mother or father to take advice on day to day circumstances, parents non support on non -academic activities, distress due to parents enforcement on school activities were found to be associated with higher percentage of mental health problems in adolescence. The study identified the importance of urgent identification and treatment of victims of tsunami who were having persistence psychological problems. It also highlights the importance of having a school based mental health service with aims of screening and developing mental well-being at school